Born of the Sun : Seven Young Australian Lives. - Walsh, Gerald (Pandanus Books, 2006)
Born of the Sun records the lives of seven young Australians who achieved widespread fame in their fields of endeavour between 1866 and 1933-- rowing, rugby, swimming, boxing, cricket, medical research and on the battlefield --and who all died in the plenitude of youth. In doing so, it offers fascinating insights into Australia's coming of age. This lively account illuminates the lives of Harry Searle, Lonnie Spragg, Barney Kieran, Les Darcy, Archie Jackson, Professor John Hunter and Lieutenant Eric Edgerton.